The Filipino young adult novel a safe place - Alipon, Perpilili Vivienne E. (2008)
"I Hate my Mother!" is a young adult novel about three women in the family - Bell, the 16-year old college freshman who hates her mother, her sister Cory, and their mom. The novel follows Bell's journey as she faces the typical challenges of a teenager while struggling to assert her independence as she discovers the person she is. The critical essay, entitled "The Filipino Young Adult Novel : A Safe Place," explores the central issue of the novel -- parent-teen conflict/relationship -- from a socio-psychological perspective, and how Filipino young adults relate to this issue. What is also given much consideration is the life stage in which this issue is being experienced -- that of the adolescent stage -- when the search for identity as faced by the adolescent are the basis for the essay's assertion that the young adult novel can be a formidable medium for the adolescent in finding the assurance that one seeks or needs to overcome the tasks of the stage.